Overview of Molecular Genetic Diagnosis. (1st January 2013) - Harada, Shuko; Korf, Bruce R.
Abstract: This unit describes the overview and strategies for molecular genetic diagnosis. Molecular genetic testing is typically used to detect changes in a single gene, and includes direct sequence analysis and detection of large deletion/duplication. Occasionally linkage analysis is still used when the gene is not known. Direct mutation analysis is possible if the gene responsible for a disorder has been identified. Genetic linkage analysis is used when polymorphic markers are available that are closely linked to a disease gene but the gene itself has not been cloned, or when it is difficult or impossible to detect mutations in the gene. For direct mutation analysis, the unit offers a review of the types of mutations that can be detected and the strategies that can be employed for their detection. The unit then describes the types of disorders that are best suited for linkage‐based analysis and offers guidance for interpreting the data. The unit also overviews recent progress on high‐throughput sequencing system and its possibility for its clinical application. Curr. Protoc. Hum. Genet . 76:9.1.1‐9.1.7. © 2013 by John Wiley & Sons, Inc.